INDONESIA'S ECONOMIC STRUCTURE TRANSFORMATION 2026: FROM DEFENSIVE STABILITY TO ACCELERATED UPSTREAM PROCESSING AND AN INCLUSIVE DIGITAL ECONOMY - Mohd Syahrin; Muhani (INJOSEDU: International Journal of Social and Education, 2026)
This article analyses the transformation of Indonesia's economic structure in 2026, which will shift from a defensive stability strategy—with stable GDP growth of 5.11 per cent in 2025—towards accelerating upstream processing (mineral, energy and agricultural downstreaming) and an inclusive digital economy as pillars of national sovereignty. The method used in this study is a literature review. The results show that the downstreaming programme targets Rp3,464.5 trillion in investment to create 1 million jobs and USD50 billion in added value, while the digital ecosystem targets USD146 billion in the digitisation of 20 million MSMEs and equitable access in 3T regions. The integration of these two pillars, supported by the PDP Law regulations and Industry 4.0 upskilling, has the potential to increase the contribution of digital manufacturing to GDP to 35 per cent by 2030, although the challenges of regional disparities and human resources need to be addressed through the synergy of the state budget and green growth engines to achieve the 8 per cent growth target and Indonesia Emas.